Chromerid genomes reveal the evolutionary path from photosynthetic algae to obligate intracellular parasites - Woo, Yong; Ansari, Hifzur; Otto, Thomas; Linger, Christen; Olisko, Martin; Michálek, Jan; Saxena, Alka; Shanmugam, Dhanasekaran; Tayyrov, Annageldi; Veluchamy, Alaguraj; Ali, Shajahan; Bernal, Alex; et al. (eLife Sciences Publications Ltd, 2015)
The eukaryotic phylum Apicomplexa encompasses thousands of obligate intracellular parasites of humans and animals with immense socio-economic and health impacts. We sequenced nuclear genomes of Chromera velia and Vitrella brassicaformis,free-living non-parasitic photosynthetic algae closely related to apicomplexans. Proteins from key metabolic pathways and from the endomembrane trafficking systems associated with a free-living lifestyle have been progressively and non-randomly lost during adaptation to parasitism. The free-living ancestor contained a broad repertoire of genes many of which were repurposed for parasitic processes,such as extracellular proteins,components of a motility apparatus,and DNA- and RNA-binding protein families. Based on transcriptome analyses across 36 environmental conditions,Chromera orthologs of apicomplexan invasion-related motility genes were co-regulated with genes encoding the flagellar apparatus,supporting the functional contribution of flagella to the evolution of invasion machinery. This study provides insights into how obligate parasites with diverse life strategies arose from a once free-living phototrophic marine alga. © Woo et al.
Keywords: Alga; Apicomplexa; Chromera velia; Gene expression; Genome analysis; Host parasite interaction; Molecular evolution; Nonhuman; Parasite; Phylogeny; Polymerase chain reaction; Protein localization; RNA isolation; Sequence alignment; Transcription regulation; Vitrella brassicaformis; Alveolata; Chemistry; DNA sequence; Gene expression profiling; Genetics; Molecular genetics; Algae; Animalia; Eukaryota; Algal DNA; Alveolata; DNA; Algal; Evolution; Molecular; Gene Expression Profiling; Molecular Sequence Data; Sequence Analysis; 24 Ciencias de la Vida; ODS 14 - Vida submarina; ODS 15 - Vida de ecosistemas terrestres